A Study on Preparation and Properties of Starch from Deep-purple Corn - Rasamee Supasri; Vipa Surojanamatakul (Agriculture and Natural Resources, 1993)
Starch was isolated from a variety of deep-purple corn (DPC) by wet-milling process. The use of suitable starch table could provide good protein-starch separation. The data on chemical and physical properties of the DPC starch was compared to those of Maizena, McGarett and Friendship, the three commercial starches. Chemical compositions and starch contents of the DPC starch and the others were quite similar. Protein, fat and crude fiber contents which indicate the starch quality were lower. The DPC starch granule size (7.65 - 22.95 micron) was a little wider range than those of the three commercial ones. Microscopic examinations, both light and scanning electron, of the starch granules were measured. The DPC starch had more white color, somewhat higher water and oil -absorptions and higher solubility and swelling power than those of the commercial ones, but similar in gelatinization temperature range. It’s degree of syneresis was lower than that of McGarett. Brabender viscosity patterns of the DPC starch and the commercial ones were quite similar. The DPC starch presented peak viscosity (660 B.U.), set-back (440 B.U.), consistency (630 B.U.) and breakdown (190 B.U.) upon continual cooking.